(untitled) (Journal of the College of Basic Education, 2022)
Research study was that climatic factors a significant impact on air pollution in the city of Baghdad، where the effect of each element on the other is different، and through the importance of the study noted that the wind and dust storms، temperature، precipitation and other atmospheric disturbances important role in the deployment of air pollution in the study area، where the influence wind and dust storms in the smoke movement and other air pollutants and reflected the impact of those air pollutants on the nature of precipitation، where the resulting acid rain and smog (haze)، which in turn، negative effects on the local environment and the environment of cities and observe through the study of air pollutants are concentrated in the cities than the countryside and open areas. It summarized the study found that air pollution in the city of Baghdad، heavily influenced by the nature of climatic elements in the dissemination of pollutants and concentration where he studied researcher sources of pollution in the study area، such as gas، cars and power plants، factories and dust storms.